Thermodynamic Study of Comfarol Binding to Urease - Zolghadr, Leila; Behbehani, Gholamreza Rezaei; Divsalar, Adeleh; Moubarakabadi, Zahra (Orbital: The Electronic Journal of Chemistry, 2019)
Isothermal Titration Calorimetry, ITC, was used to study of Jack Bean urease, JBU, binding with comfarol in phosphate buffer at pH 7.4. Data analyzing of comfarol interaction with JBU was performed by the extended solvation model and the positive cooperativity of comfarol with JBU indicates that comfarol causes stabilization of the JBU structure. DOI: http://dx.doi.org/10.17807/orbital.v11i3.1369